Ending Poverty by Encouraging Business, Not Aid - Jing Zhao; Glenn Shinn (Journal of International Agricultural and Extension Education, 2012)
After decades of aid programs from wealthy countries, 49 least developed countries and some 2.5 billion people remain destitute and steeped in poverty. The literature is replete with proposed solutions to improve livelihoods and lift economies; however, the results have been disappointing. Aid Trap authors R. Glenn Hubbard, dean of Columbia Business School, and William Duggan, a senior lecturer, are experienced in business policy and development practice. They argue equivocally “business is the only solution” (p. 3).
Keywords: Africa; Agricultural Development; Business; Capacity Building; Charity Aid; China; Education; NGO; Marshall Plan; Poverty